DOES THE QUALITY OF INTERNAL AUDIT IN THE NORTH SUMATRA GOVERNMENT BECOME IMPACTED BY SUPERIOR'S ORDERS? - Yulisfan; Erlina; Idhar Yahya; Zulkarnain (Universitas Efarina, 2022)
The objective of this study is to examine the potential impact of superior’s orders on the quality of internal audits conducted inside the North Sumatra Government. The primary objective of this research is to ascertain the dynamics and determinants that exert an influence on the conduct of internal auditors when confronted with directives or coercion from higher-ranking individuals, and to examine the subsequent ramifications on the quality of audits produced. This study examines the factors that influence the behavior of internal auditors when they encounter pressure to fulfil organizational demands, and the potential consequences on the quality of the audit process and outcomes. The present study examines the impact of superior’s orders on professional standards, ethical conduct, and the overall efficacy of the internal audit function. The research methodology employed in this study involves the utilization of a survey method approach, wherein a representative sample of internal auditors within the North Sumatra Government is collected. The present study employs the Partial Least Squares (PLS) methodology to examine the association among variables. This study aims to identify the primary factors that lead to the variation in Internal Audit Quality (IAQ), with a specific focus on the issues encountered by internal auditors who work inside intricate government settings. The aforementioned discoveries not only constitute a valuable contribution to the scholarly conversation surrounding the influence of compliance demands and professional conduct, but they also provide practical knowledge for policymakers and practitioners who aim to enhance the efficiency of internal audit practices within the public sector. This study adds to the expanding corpus of literature about the behavioral dimensions of internal audit and offers empirical findings that might guide efforts to enhance the quality of audits in governmental organizations, specifically within the distinct setting of North Sumatra.